SKRINING FITOKIMIA DAN UJI AKTIFITAS ANTIBAKTERI EKSTRAK DAUN TELANG (Clitoria ternatea L.) TERHADAP BAKTERI Pseudomonas aeruginosa - Lia Fikayuniar; Ermi Abriyani; Sabila Nur Safitri; Didi Jayadi Mulya (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2022)
Telang leaf (Clitoria ternatea L.) is one of the plants that is often used as a traditional medicine by the people of Indonesia to cure infections which is used by attaching it to the sore, wound or swollen part. The purpose of this study was to determine the antibacterial bioactivity of n-hexane, ethyl acetate, and methanol extracts of telang leaf against Pseudomonas aeruginosa bacteria and to determine the content of secondary metabolites in the extracts of n-hexane, ethyl acetate, and methanol qualitatively by phytochemical screening and thin layer chromatography. The method used in this study is the antibacterial method of pitting with a concentration of 40%, 60%, 80%, 100%, phytochemical screening, and thin layer chromatography with specific spot appearance. The best potential antibacterial bioactivity between n-hexane, ethyl acetate, and methanol extract of telang leaf (Clitoria Ternatea L.) against Pseudomonas aeruginosa is the methanol extract of telang leaf (60%) which has an inhibition zone of 18.57 mm, strong category and based on supporting data. qualitatively by phytochemical screening containing secondary metabolites, namely flavonoids, saponins, tannins, quinones, polyphenols and triterpenoids/steroids as well as TLC results with the appearance of specific Liebermen burchard (LB) spots that are positive blue-black in color, suspected as an antibacterial of the triterpenoid/steroid secondary metabolite group.